Chemistry and pharmacology of some plants mentioned in the letter of Pero Vaz de Caminha - Alves, Lucio F.; Ming, Lin C. [UNESP] (Univ Estadual Paraiba, Editora-eduep, 2015)
Brazil has a long tradition in the study of medicinal plants. When the Portuguese arrived to the new colony, Pero Vaz de Caminha, the scriber of the fleet, left the first impressions of the local and the inhabitants. He clearly mentions how the Indians use natural dye as tincture to paint their bodies. This article reviews the phytochemical and pharmacological characteristics of these colorants and other medicinal plants recently identified mentioned in this letter.
Keywords: Ethnobotany; Historical ethnobiology; Medicinal plants; Natural products